Olahan kelapa dan singkong untuk kemajuan desa pematang tujuh kecamatan rasau jaya kalimantan barat - Agato Agato; Kardison Lumban Batu (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
Coconut and cassava are known as multi-functional plants that can be processed into various food and non-food preparations. In food processing using coconut using water and fruit flesh into a variety of food preparations that have economic value, while cassava can be used for tubers and parts of the skin. The processing of coconuts and cassava is aimed at farmer groups in Pematang Tujuh village, Rasau Jaya District, West Kalimantan. The purpose of this activity is the formation of a diversified group of coconut and cassava based products, so that work partners have an entrepreneurial spirit as measured by the formation of a small business group of processed coconut and cassava products, as well as having the ability to open market share and form new marketing networks. The method used is to begin with the delivery of information on opportunities that might be created from the local potential of Pematang Tujuh village and the guidance of new business management to achieve the success of the proposed program. This is followed by a comprehensive processing and management system for various processed coconut and cassava starting from the production, operation of machines and equipment, storage packaging systems and a complete management system for opening new businesses. The results obtained are all participants can do the processing of products from coconut and cassava